Assessment of Competition in EU Liberalised Energy Markets in 2016 - Kádár-Horváth, Ágnes (Theory, Methodology, Practice – Review of Business and Management, 2017)
The liberalisation of gas and electricity markets had been achieved in almost all EU Member States by the end of the last century. It basically aimed at bringing competition into energy markets and benefiting from its favourable impacts. However, initial experiences showed that markets suffered from limited competition. The objective of this article is to give a brief assessment of the current market competition with special attention to two fundamental issues related to undistorted competition: unbundling of activities and developments in market concentration. The analysis shows that significant progress has been achieved in the unbundling of activities over the past few years. However, the market concentration in the retail segment in most Member States is still high (based on the HHI, C3, the number of undertakings with a market share over 5 percent, and the ARCI indicators).